Investigating the role of pharmacogenomics in personalizing medication therapy for children: a pilot study - Sahu, Prerana; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
An antimetabolite that is frequently given for the treatment of both adult and pediatric malignancies is methotrexate (MTX). Because of MTX-related toxicity and pharmacokinetic unpredictability, HDMTX treatment is challenging. Methotrexate disrupts the metabolism of folate by blocking the methylenetetrahydrofolate enzyme (MTHFR). MTHFR polymorphism may affect how well a patient tolerates MTX. Therefore, the study intends to connect the clinical outcome of pediatric ALL patients receiving HDMTX infusions with the serum methotrexate level and MTHFR polymorphism. Between February 2023 and May 2024, a prospective study was conducted at CMC Hospital in Vellore. Acute Lymphoblastic Leukemia (ALL) relapses in children who were younger than 18 years old at enrollment and who are on high doses. Serum methotrexate levels 48 hours following the initiation of HDMTX infusion may be associated with severe methotrexate toxicity. While most patients with the A1298 C homozygous mutant (CC) exhibited increased liver enzymes, we observed that patients with the C667 T variation (CT) had delayed methotrexate elimination. MTHFR genotyping and serum methotrexate drug level prediction are crucial for preventing toxicities in individuals receiving high doses of methotrexate infusion.